The role of androgens in follicle maturation and ovulation induction: friend or foe of infertility treatment? - Gleicher Norbert; Weghofer Andrea; Barad David H (BMC, 2011)
Abstract Background Effects of androgens on follicle maturation have been controversial for some time. Here, we review the potential of their applications in improving human ovulation induction, based on human and animal data, reported in the literature. Methods We reviewed the published literature for the years 2005-2011, using relevant key words, in PubMed, Medline and Cochrane reviews, and then performed secondary reviews of referenced articles, which previously had not been known or preceded the searched time period. A total of 217 publications were reviewed. Results Contrary to widely held opinion, recent data, mostly developed in the mouse, convincingly demonstrate essential contribution of androgens to normal follicle maturation and, therefore, female fertility. Androgens appear most engaged at preantral and antral stages, primarily affect granulosa cells, and exert effects via androgen receptors (AR) through transcriptional regulation but also in non-genomic ways, with ligand-activated AR modulating follicle stimulating hormone (FSH) activity in granulosa cells. While some androgens, like testosterone (T) and dehydroepiandrosterone (DHEA), appear effective in improving functional ovarian reserve (FOR) in women with diminished ovarian reserve (DOR), others may even exert opposite effects. Such differences in androgens may, at least partially, reflect different levels of agonism to AR. Discussion Selective androgens appear capable of improving early stages of folliculogenesis. They, therefore, may represent forerunners of a completely new class of ovulation-inducing medications, which, in contrast to gonadotropins, affect follicle maturation at much earlier stages.